2023
DOI: 10.3390/ma16145018
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Aid Effect of CuO-TiO2-Nb2O5 on the Dielectric and Structural Properties of Alumina Ceramics

Rafael I. Shakirzyanov,
Natalia O. Volodina,
Kayrat K. Kadyrzhanov
et al.

Abstract: The aim of this work is to study the structural, dielectric, and mechanical properties of aluminum oxide ceramics with the triple sintering additive 4CuO-TiO2-2Nb2O5. With an increase in sintering temperature from 1050 to 1500 °C, the average grain size and the microhardness value at a load of 100 N (HV0.1) increased with increasing density. It has been shown that at a sintering temperature of 1300 °C, the addition of a 4CuO-TiO2-2Nb2O5 additive increases the low-frequency permittivity (2–500 Hz) in alumina ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…The analysis of the phase composition of the sintered samples using the XRD and Raman spectroscopy methods made it possible to clarify the known phase diagrams of the ZrO 2 -CeO 2 system, namely, to determine the areas of formation of the pure tetragonal ZrO 2 -t phase and the ZrO 2 -t+ ZrO 2 -c mixture (predominance of the t-phase), as well as the region of formation of substitutional solid solutions with a fluorite crystal structure. Density measurements and porosity evaluations of the resulting ceramics showed that porosity decreased with decreasing x values above x = 0.25, while density varied non-monotonically within the range of 5.6-6.2 g/cm 3 . Below this concentration, a significant decrease in density, shrinkage, and an increase in porosity was observed due to the formation of cracks due to the martensitic transition t→m upon cooling.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The analysis of the phase composition of the sintered samples using the XRD and Raman spectroscopy methods made it possible to clarify the known phase diagrams of the ZrO 2 -CeO 2 system, namely, to determine the areas of formation of the pure tetragonal ZrO 2 -t phase and the ZrO 2 -t+ ZrO 2 -c mixture (predominance of the t-phase), as well as the region of formation of substitutional solid solutions with a fluorite crystal structure. Density measurements and porosity evaluations of the resulting ceramics showed that porosity decreased with decreasing x values above x = 0.25, while density varied non-monotonically within the range of 5.6-6.2 g/cm 3 . Below this concentration, a significant decrease in density, shrinkage, and an increase in porosity was observed due to the formation of cracks due to the martensitic transition t→m upon cooling.…”
Section: Discussionmentioning
confidence: 96%
“…The tangent loss frequency dependencies also showed pronounced dispersion throughout the whole measured range. This feature can be explained by the relatively high conductivity of ceramics [3]. If a metal oxide consists of multivalence cations, its conductivity becomes higher due to the hopping electron mechanism [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all the samples, the apparent density and porosity were calculated using the X-ray density values (Table 1). The highest HV0.2 value was obtained for the least porous sample, which demonstrates a pronounced dependence of microhardness on the presence of pores in the sample [48,49]. On the other hand, despite the decrease in apparent density (increase in porosity), in some cases, it was observed that microhardness does not follow the change in apparent density (e.g., sample with two annealings and concentration x = 0.2).…”
Section: (E)mentioning
confidence: 89%